The evolution of the mandarasals in Quiapo: an enthnography of cultural studies - Sarah Joy M. Lavapie. 4 0 16; 5 (2012)
u
Undergraduate Thesis: (Bachelor in Mass Communication) - Pamantasan ng Lungsod ng Maynila, 2012.
Keywords: 2 -- 0; 6; 20; 20; 2